Multicultural Collaboration to Optimize Early Childhood Development in Kindergarten - Angraini Daboti; Nabila Al Qammah Putri; Nadhiva Aulia Gusva; Novelya Triye Mulyawi; Gebilla Dwi Yonanta; Mutiara Nafisa (CV Berkah Syahdin Trust, 2026)
Background: Early childhood education plays a crucial role in shaping children’s cognitive, social-emotional, language, and motor development. In multicultural societies such as Indonesia, the diversity of cultural, social, and religious backgrounds presents both opportunities and challenges in creating inclusive and effective learning environments. However, the lack of structured collaboration between schools, families, and communities often limits the optimization of children's holistic development. Aims: This community service program aims to enhance early childhood development through the implementation of multicultural collaboration involving teachers, parents, and the community in a kindergarten setting. Methods: This program employed a participatory and collaborative approach consisting of three main stages: preparation, implementation, and evaluation. The preparation stage involved needs analysis, coordination with the school, and development of multicultural-based learning materials. The implementation stage included interactive activities such as storytelling, singing, role-playing, and motoric games reflecting cultural diversity. The evaluation stage was conducted through discussions with teachers and observations of children’s development. Participants included 50 children and parents, as well as 6 teachers at UPTD TK Negeri Pembina Sungai Tarab. Result: The results indicate that the program contributed positively to children’s development, particularly in social interaction, self-confidence, and attitudes of tolerance and respect for diversity. In addition, teachers showed improved understanding and ability to integrate multicultural values into daily learning activities. The collaborative approach also strengthened the relationship between school, family, and community. Conclusion: Multicultural collaboration is an effective approach to optimize early childhood development in an inclusive learning environment. The program not only enhances children’s holistic development but also strengthens the synergy among educational stakeholders, making it a sustainable and replicable model for early childhood education practices